Intact in vivo visualization of telencephalic microvasculature in medaka using optical coherence tomography - Suzuki, Takashi; Ueno, Tomohiro; Oishi, Naoya; Fukuyama, Hidenao (Scientific reports, 2020)
To date, various human disease models in small fish—such as medaka ( Oryzias lapties )—have been developed for medical and pharmacological studies. Although genetic and environmental homogeneities exist, disease progressions can show large individual differences in animal models. In this study, we established an intact in vivo angiographic approach and explored vascular networks in the telencephalon of wild-type adult medaka using the spectral-domain optical coherence tomography. Our approach, which required neither surgical operations nor labeling agents, allowed to visualize blood vessels in medaka telencephala as small as about 8 µm, that is, almost the size of the blood cells of medaka. Besides, we could show the three-dimensional microvascular distribution in the medaka telencephalon. Therefore, the intact in vivo imaging via optical coherence tomography can be used to perform follow-up studies on cerebrovascular alterations in metabolic syndrome and their associations with neurodegenerative disease models in medaka.